Pengaruh Jaringan Usaha, dan Minat Usaha Terhadap GCG Serta Implikasinya Pada Informasi Akuntansi UMKM Kota Medan - stefvy stefvy (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
Accounting information is very important for every business, both MSMEs and large businesses, one of the factors that causes failure in developing a business is due to a lack of understanding of accounting information, especially for MSMEs, as well as the need to foster business networks and strong business interests and MSMEs also need to apply principles or principles. the principle of good corporate governance. This study aims to determine the effect of business networks and business interests on the use of accounting information in small and medium enterprises with good corporate governance as an intervening variable. The sample in this study amounted to 152 respondents who were in the city of Medan. The sampling technique used purposive random sampling and the data collection technique was using a questionnaire, and distributed directly to the respondents. Data analysis in this study used path analysis with SEM. The results of testing the hypothesis indicate that there is a positive and significant influence between business networks, business interest in accounting information and Good Corporate Governance.